The Influence of Perceptions of Social Support and Family Health Tasks on HIV/AIDS Prevention Behavior in Adolescents - Diah Ratnawati; Nourmayansa Vidya Anggraini (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2021)
Adolescents are physically and psychologically vulnerable to the transmission of HIV/AIDS, so that they become the focus of the population for disease prevention programs. This study aims to determine the effect of perceptions of social support and family health tasks on HIV/AIDS prevention behavior in adolescents in Baros Village, Serang, Banten. This study employed a quantitative research method with a cross-sectional design. The number of samples was 345 adolescents who were at risk of HIV/AIDS in Baros Village, Serang, Banten. Sampling from each class administering stratified sampling method. Researchers reproduced research questionnaires with an offline system which had previously been examined for the validity and reliability of a number of samples that have been calculated. Furthermore, for research questionnaires with an online system, distribution is conducted via a link from the google form. The chi-square test was administered to examine HIV/AIDS prevention behavior variables. A logistic regression test was used to see the most influential factors on HIV/AIDS prevention behavior. The results revealed a relationship between gender and family health tasks in recognizing HIV/AIDS prevention behavior problems in adolescents in Baros Village, Serang, Banten, with a p-value <0.05. The factor that most influenced HIV/AIDS prevention behavior was the family health task in recognizing problems with a p-value of 0.007 <0.05 with the largest OR value obtained, which is 1.978. Therefore, families should improve their ability to conduct health tasks in communicating and directing adolescents in HIV/AIDS prevention behavior.